Implementation Methods for Shearwall SW2 Casting in Institutional Buildings - Reynold Andika Pratama; Asri Winita; Al Hapizd Muhamad Rizky; Kartika Setiawati (Asosiasi Dosen Muda Indonesia, 2025)
Each building must be built as best as possible to meet the feasible technical criteria in terms of quality, ethics, and aesthetics. In addition, the building must also meet the cost and administrative criteria for dormitory buildings and supporting facilities. The STAN Bintaro student dormitory building construction project consists of the lower structure (foundation), upper structure, and finishing work. In this practical work report, it focuses on one of the superstructure works, namely the work of the sliding wall or shear wall and the special purpose is to know the casting method of the shear wall in the construction project of the STAN Bintaro student dormitory building. Based on the results of observations during the practical work, the method in the implementation of the shear wall casting work itself starts from the determination of the axle, fabrication of reinforcement, installation of reinforcement, installation of formwork, casting, removal of formwork and then ends with shear wall maintenance. The data obtained regarding the dimensions of the shear wall in type SW2 is 5700 mm long with a thickness of 400 mm, for the reinforcement used, namely 6D16 reinforcement and D16-100 rebar. The quality of the concrete used is K-350. Future methods of casting implementation must continue to explore innovative solutions, such as the use of sophisticated materials and potimalized schemes, to further improve the performance of these structural components.